Clinical characteristics and economic burden of tuberculous-destroyed lung in Korea: a National Health Insurance Service-National Sample Cohort-based study - Lee, Hwa Young; Han, Deok Jae; Kim, Kyung Joo; Kim, Tae Hoon; Oh, Yeon-Mok; Rhee, Chin Kook (Journal of Thoracic Disease; Vol 11, No 6 (June 29, 2019): Journal of Thoracic Disease, 2019)
Background: Tuberculous destroyed lung (TDL) contributes to patient mortality via acute exacerbation and combined medical comorbidities. This study characterized the clinical characteristics and economic burden of patients with TDL using large scale database, Health Insurance Review and Assessment Service (HIRA) data. Methods: We searched the HIRA national database to identify patients diagnosed with TDL from January 01, 2011 to December 31, 2015. The clinical characteristics of the patients were collected and the 5-year claims data were analyzed. Results: In total, 645,031 patients (55% male, mean age, 59.6 years) were enrolled over the 5 years. During the study period, 98.5% of the patients visited a primary care clinic and 71.1% and 93.2% visited secondary and tertiary hospitals, respectively. Patients spent a median of 5 days for inpatient services, and were admitted to the hospital a median of 0.62±1.2 times per person annually. Annual total cost per person was $1,838 and half of the total cost was expended for inpatient services. About 68.9% of the patients were prescribed respiratory medications, and $12 million was paid. Oral bronchodilators (46.5%) and methylxanthine (35.2%) were used more frequently than inhaled corticosteroids (ICSs)/long-acting β2 agonist (LABA) combination agents (11.6%) or inhaled long-acting muscarinic antagonists (LAMAs) (7.5%). Conclusions: TDL imposes a high medical economic burden in Korea. The estimated economic costs were mainly made up of inpatient services and outpatient medication prescriptions. Interventions to prevent acute disease exacerbations and progression of comorbid conditions should be accompanied to alleviate the clinical and economic burden of TDL.